ETNOMATEMATIKA ANGKLUNG PAGLAK BANYUWANGI - NUR HIDAYATULLOH; Rachmaniah Mirza Hariastuti (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Angklung Paglak is a typical Banyuwangi angklung musical instrument that is heard from above using the tone of the Banyuwangian genre. Angklung Paglak has many things that can be explored to be used with mathematical concepts. The purpose of this study is to find out mathematics concept in angklung paglak Banyuwangi This research is exploratory-descriptive research. Data collection is done by literature review, observation, interviews and documentation. Data were analyzed by qualitative methods. The results of this study indicate that: (1) The characteristics of angklung paglak Banyuwangi in terms of shape and process are the same as the other Banyuwangi angklung types. Angklung paglak and other Banyuwangi angklung have differences in terms of many players. Paglak angklung players were 4 people, 2 angklung players and 2 drums players while the other Banyuwangi angklung players varied. (2) The mathematical concept in angklung paglak is about two or three-dimensional geometric shapes; traditional measurement units; concept of equating length to an object; and concept of equating length to an object.